EROSI IMAN DI ERA DISRUPSI: REINTERPRETASI IRTIDĀD DALAM QS. AL-MĀ'IDAH: 54 MELALUI VARIASI QIRĀ'ĀT - Siti Amelia; Hananajma Muharromah; Naima Aziza; Najib Irsyadi (Jurnal Riset Multidisiplin Edukasi, 2026)
This article investigates how the variation of Qur'anic readings (qirā'āt) in QS. al-Mā'idah: 54 opens a new semantic space for reinterpreting the gradual erosion of religious commitment among contemporary Muslim netizens a phenomenon termed "digital faith erosion." Through qualitative library research employing an interdisciplinary approach (linguistic-qirā'āt analysis, comparative tafsīr, and religious identity theory), this study finds that the morphological difference between yartadda (idghām, majority reading) and yartadid (iẓhār, Ḥamzah and al-Kisā'ī) generates two distinct semantic layers: (1) formal/legal riddah denoting an abrupt, decisive act of apostasy and (2) symbolic/gradual riddah reflecting a slow, iterative erosion of spiritual commitment occurring in digital spaces through exposure to nihilism, religious relativism, and algorithmic consumerism. Classical exegetes (al-Ṭabarī and Ibn Kathīr) contextualise the verse within the historical Ridda Wars, adopting a political-military hermeneutic.  Contemporary exegetes (Ibn 'Āshūr and Quraish Shihab), by contrast, foreground the communal dimensions of spiritual resilience expressed through the verse's core triad: yuḥibbuhum wa yuḥibbūnahū (reciprocal love), adhillah 'alā al-mu'minīn (solidarity), and lā yakhāfūna lawmata lā'im (moral courage). This study contributes a novel theoretical framework integrating 'Ulūm al-Qur'ān with the Sociology of Digital Religion and argues that qirā'āt is not merely a technical discipline but a rich hermeneutic instrument for addressing the fragility of faith in the digital age.